Situational Conditions for Sports Tourism in Achieving Competitive Advantage in North Rift Region of Kenya - Tubey , Ruth Jelagat; Tubey, Winnie (African Journal of Education,Science and Technology (AJEST), 2015)
While there are many tourism products, sports tourism has increasingly become one of the most popular products. In order for any country to benefit from sports tourism, it needs to have the necessary conditions that can make the industry to flourish. Several authors cite several explanations including environmental factors, psychological advantage and favorable physiological characteristics, which may be genetically conferred or environmentally determined. This paper seeks to establish the situational conditions existing in the North Rift region that prompt sports tourism. The study adopted a descriptive survey design and was guided by the integrated model for destination competitiveness by Dwyer et al. (2004). Target population included all the athletics camps and the tourism facilities in Uasin Gishu and Nandi districts. Simple random sampling was used to select 25 athletics camps from which 50 athletics officials were selected using simple random sampling technique. One manager from each of the tourism firms was also selected for the study, making a total of 35 tourism firm managers. Primary data was collected by use of structured questionnaires, while secondary data was collected through critical examination of public or private recorded documents related to the study. Data was analyzed using techniques which included frequencies, means, modes, standard deviation and percentages. The region received a fair rating in terms of the general business environment and a good review in terms of political stability and tourists‘ safety and security. It is hoped that the findings of the study will be useful to tourism policy makers and other interested stakeholders in designing strategies and policies, as well as support them to make relevant decisions regarding the North Rift region sports tourism. It further seeks to highlight the competitive advantage of the region as a sports destination.